'It's the best job in the world, but one of the hardest, loneliest, most misunderstood roles in a school.' Understanding the complexity of the SENCO role post‐SEND reform. Issue 1 (31st January 2021) - Curran, Helen; Boddison, Adam
Abstract: In schools, the Special Educational Needs Coordinator (SENCO) could be considered a key policy implementer of special educational needs and inclusive policy. Issues related to time, status and the effective facilitation of the SENCO role have been reported on extensively, yet literature has predominantly focused on the role prior to the introduction of the Special Educational Needs and Disability (SEND) reforms in 2014. This paper reports on research which explored the SENCO role post‐reform. The research aimed to understand how widely the role varied across differing educational settings and phases, whilst also exploring the breadth and depth of the role, post‐SEND reform. The research design was mixed methods and had two phases: online focus groups (n = 15), followed by a national online survey (n = 1903). The findings suggest that the facilitation of the SENCO role remains problematic post‐reform. Constraints include the time to undertake responsibilities, the increasing breadth of the role and how the role is understood by others. This combined with increased external bureaucracy, budgetary constraints and a lack of consistency nationally has led to a situation where only approximately one‐third of SENCOs intend to remain in the role in five years' time.